FACTORS TO CONSIDER WHEN CREATING A BUSINESS UNIT - Vargas, Auxiliadora; Diez1, Said; Acosta, Nadia (Revista Inclusiones, 2020)
The main objective of this paper is to identify the factors to consider in creating a business unit. In order to achieve this aim and as part of the methodology, a literature review of the concepts, findings and contributions of several authors was carried out by consulting the database of scientific journals in SCOPUS. After the revision and the analysis and discussion, this paper concluded that the Cultural and Social Standards (CSS) and the Entrepreneurial Capacity (EC) are the most significant factors to appraise when creating a new business.